Prevalence of Intestinal Parasitic Infections among Patients of King Fahd Medical City in Riyadh Region, Saudi Arabia: A 5-Year Retrospective Study - Omar S. O. Amer; Esam S. Al-Malki; Mohamed I. Waly; Abdulaziz AlAgeel; Mahmoud Y. Lubbad (Journal of Parasitology Research)
This study is a retrospective analysis of the recorded intestinal parasitic infections for in- and outpatients visiting King Fahd Medical City, Riyadh, Saudi Arabia, from 2013 to 2017. In this study, a total of 5987 in- and outpatient were examined for intestinal parasitic infection. 30 patients out of 5987 were infected with 6 species of intestinal parasites with prevalence rate 0.5%. These parasites were Entamoeba histolytica (P = 0.27%), Cryptosporidium sp. (P = 0.1%), Giardia lamblia (P = 0.07%), Trichuris trichiura (P = 0.03%), Hymenolepis nana (P = 0.02%), and Chilomastix mesnili (P = 0.02%). The prevalence of infection in both males and females was 0.38% and 0.58%, respectively. Also, the prevalence of infection in different years and age groups as well as different seasons was provided. Intestinal parasitic infections are still a public health problem in Riyadh region, Saudi Arabia. Updating the epidemiologic survey of these parasites at regular intervals using the appropriate statistical methods is necessary to develop effective prevention and control strategies.